A brief review of the complexities of teaching and learning chemical equilibrium with specific reference to Malaysia - Chandrasegaran, Chandra; Treagust, David; Mocerino, Mauro; Won, Mihye; Karpudewan, M. (eprints@NUY, 2014)
The purpose of this study was to review the extant literature on chemical equilibrium research in high school chemistry. The review involved understanding of the nature of chemical equilibrium, particularly about chemical reactions not going to completion, the reversibility of chemical reactions and the idea of dynamic equilibrium. Associated with these understandings was the derivation of the Equilibrium Law and the significance of the equilibrium constant followed by the use of Le Chatelier's Principle including the limitations of this principle. The review then focused on the common alternative conceptions associated with the chemical equilibrium concept. The study next considered these features in the Malaysian context. For this purpose, the researchers formulated an instructional program relevant to the Malaysian Higher School Certificate curriculum that was implemented over 11 hours with 56 high-achieving students in Year 12 from a private secondary school. To evaluate students' understanding of chemical equilibrium concepts after instruction the Chemical Equilibrium Conceptual Test-1 (CECT-1) was administered after instruction. The test consisted of 10 two-tier multiple-choice items that were adapted from previously developed questionnaires. The results indicated very limited understanding of the relevant concepts. The total scores in the CECT-1 ranged from 0 to 9 (out of a maximum score of 10) with a mean score of 5.04. Less than 50% of students correctly answered five of the 10 items. The findings suggest the need for teachers to address students' preconceptions about chemical equilibrium concepts and use appropriate strategies to enable students to acquire scientifically acceptable understandings .